For Structural-Semantic Perception of Georgian Short Prose Titles - Geldiashvili, Nunu ("Intercultural Dialogues" Transactions, 2021)
We consider the analysis of the linguistic aspects of titles as one of the important components of the study of Georgian short prose, as it is an integral part of the text and a kind of mediator with the reader. That is why the difficult task facing writers i.e. the meaning of a title which represents a phrase consisting of one or more words - is special. A poorly thought-out title can diminish the meaning of the text, or, if it effectively exceeds the content of the text, disappoint the reader. The title is also seen not only as an indicator of the author's style, but also as an expression of the artistic-cultural thinking in which it was created. In this paper, we discuss the main features of the structure and semantics of the titles of small prose samples.Most of the titles in Georgian short prose samples representone full word; there are relatively few samles of two, three, four and more-member cases. Expressionism and gradation are mainly served by lexical repetition, synonymy and antonymy. In the paper we draw the main conclusions based on the qualitative, quantitative, analysis and synthesis methods of research.